Computer vision automation system for sorting partially overlapping tiles - Hussin, Neam Tariq (2019)
Traditionally, a method of manual sorting of tiles based on color is being performed by human operators via visual inspection. This method is slow and tedious. Another automatic method has been developed using assembly line machines, but it requires a significant amount of space to operate. New automatic tiles sorting method based on color using a robotic arm is proposed in this study which is more effective and does not require large physical space.